Hydroelastic analysis of floating long viscoelastic plate in shallow water. (2022) - Koley, Santanu; Trivedi, Kshma; V, Vipin
Abstract: The present study investigates the interaction of gravity waves heading on a large viscoelastic floating structure of negligible draft in shallow water region. The flexible property of the plate is modeled using well known Euler-Bernoulli beam equation, whereas the viscosity is modeled using complex flexural rigidity parameter. The problem is solved using the eigenfunction expansion procedure. Due to the presence of complex flexural rigidity, the dispersion relation in the region covered by the plate is complex in nature, and therefore the roots of the dispersion relation are complex types. The location of the roots has been found using Matrix analysis. Finally, various results of physical interests are studied for a wide range of structural and wave parameters.